Sergiy Ovsienko (01.05.1953--25.01.2016) (Algebra and Discrete Mathematics, 2017)
The famous Ukrainian mathematician Sergiy Ovsienko passed away on January 25, 2016. It was a sorrowful event and a grievous loss for the whole Ukrainian mathematical community, especially for those who knew him closely. We knew him as a talented and original scientist, as an outstanding teacher, as a kind and sensitive person, as a good friend.